Influences of fiber reinforced polymer layer on the dynamic deflection of concrete pipes containing nanoparticle subjected to earthquake load. Issue 8 (19th May 2021) - Motezaker, Mohsen; Kolahchi, Reza; Rajak, Dipen Kumar; Mahmoud, S. R.
Abstract: A numerical solution for dynamic analysis induced by earthquake load in concrete pipes containing SiO2 nanoparticles warped by fiber reinforced polymer (FRP) layer is utilized in the present paper on the basis of Mori–Tanaka model. The FRP layer is used as reinforcement for the concrete pipe. Utilizing the cylindrical higher order shell theory, the concrete pipe is mathematically simulated and the related governing relations are derived based on. Utilizing numerical methods of Newmark and Galerkin, the dynamic displacement of the concrete pipe is obtained. The influence of FRP layer and its thickness, volume fraction and agglomeration of nanoparticle, boundary conditions and length to radius ratio of the concrete pipe is studied on the dynamic deflection of the concrete pipe. Numerical outcomes illustrate that the FRP layer can reduces the dynamic deflection significantly.